KKN PEMBERDAYAAN MASYARAKAT DESA MELALUI PROGRAM OPTIMALISASI LAHAN SEMPIT DENGAN METODE HIDROPONIK DI DESA KRAMA JAYA - Rahadi, Indah Permata Putri; Rusmawan, Dadang; Ramdani, Afni; Sariki, Yollandhita; Yaszer, Ahmad; Enjelina, Lala; Septiani, Nofi Aca; Saif, Rizqa Muayyad; Dewi, Novita (Universitas Mataram, 2023)
Kuliah Kerja Nyata (KKN) is a form of community service activity carried out by tertiary institutions. In the KKN activities carried out in Krama Jaya Village, Narmada District, West Lombok Regency, the purpose of implementing this KKN activity was to answer various social issues found, among others, in terms of implementing village administration, narrow land use, stunting prevention, environmental cleanliness, education , and agriculture. There are 4 activity methods carried out, namely (1) making agricultural samples with a hydroponic system, (2) educating pregnant and lactating women about the importance of nutritious food for children, (3) mutual cooperation cleaning the environment and also places of worship, and (4) making places rubbish. In its implementation, UNRAM Community Service students work together with the people of Krama Jaya Village in designing, building and operating a hydroponic system. The hydroponic method was chosen because it is able to maximize the use of limited land without compromising the quality of the plants. In addition, this method also reduces the risk of contamination by soil which can lead to harmful microbial contamination. During the KKN implementation period, students provided education to mothers in the village regarding the importance of balanced nutrition and nutritional intake needed for optimal children's growth. Observations showed that the implementation of the hydroponic method in narrow land was able to produce good quality vegetables. In addition, educational efforts regarding nutrition also have a positive impact in increasing public awareness of the importance of stunting prevention.